Computer-Based Human-Machine Interfaces for Emergency Operation. (3rd June 2018) - Eitrheim, Maren H. Rø; Svengren, Håkan; Fernandes, Alexandra
Abstract: Emergency operating procedures (EOPs) are fundamental for coping with emergency and accident situations in nuclear power plants. Researchers at the Halden Reactor Project have developed a design concept including computer-based EOPs and other displays to support operators during emergency situations. The computer-based procedure system includes three displays: a symptom check display intended for monitoring EOP entrance criteria, a procedure selection and overview display, and a procedure performance display. A large-screen display provides shared information viewable for all operators in the control room. This paper describes the design, implementation, and initial testing of the displays in the Halden Man-Machine Laboratory. The original paper presented at the 10th International Topical Meeting on Nuclear Plant Instrumentation, Control and Human Machine Interface Technologies (NPIC&HMIT 2017) has been revised to include empirical results from a full-scope simulator study.